Motivation, learning strategies and their relation with the level of research skills in postgraduate students. A pilot study - Alfaro Carballido, Dahiana (2017)
Objective: To determine the influence of motivation and the use of learning strategies in the level of investigative skills in postgraduate students of dentistry of the National University of San Marcos. Materials and method: Fifty-two students were surveyed representing 50% of the total, which belong to the programs of masters and specialties. 58.8% of the students were males and 41.2% of the females were randomly selected. The questionnaire of learning strategies and motivation CEAM and a questionnaire were used to evaluate the investigative skills which was previously validated. Results: We found an association between motivation, learning strategies and students' investigative abilities OR=0.14 (IC 95%: 0.04-0.6) and a moderate correlation between rs = 0.64 (p <0.001). Conclusions: Postgraduate students in dentistry have a level of investigative skills, motivation and use of mid-level learning strategies, no significant differences were found regarding the sociodemographic and educational characteristics of the students. It concludes that students using learning strategies and motivation are 0.14 more likely to have better investigative skills.